Feasibility of Prostate PAXgene Fixation for Molecular Research and Diagnostic Surgical Pathology: Comparison of Matched Fresh Frozen, FFPE, and PFPE Tissues. (January 2018) - Högnäs, Gunilla; Kivinummi, Kati; Kallio, Heini M.L.; Hieta, Reija; Ruusuvuori, Pekka; Koskenalho, Antti; Kesseli, Juha; Tammela, Teuvo L.J.; Riikonen, Jarno; Ilvesaro, Joanna; Kares, Saara; Hirvikoski, Pasi P.; et al.
Abstract : Advances in prostate cancer biology and diagnostics are dependent upon high-fidelity integration of clinical, histomorphologic, and molecular phenotypic findings. In this study, we compared fresh frozen, formalin-fixed paraffin-embedded (FFPE), and PAXgene-fixed paraffin-embedded (PFPE) tissue preparation methods in radical prostatectomy prostate tissue from 36 patients and performed a preliminary test of feasibility of using PFPE tissue in routine prostate surgical pathology diagnostic assessment. In addition to comparing histology, immunohistochemistry, and general measures of DNA and RNA integrity in each fixation method, we performed functional tests of DNA and RNA quality, including targeted Miseq RNA and DNA sequencing, and implemented methods to relate DNA and RNA yield and quality to quantified DNA and RNA picogram nuclear content in each tissue volume studied. Our results suggest that it is feasible to use PFPE tissue for routine robot-assisted laparoscopic prostatectomy surgical pathology diagnostics and immunohistochemistry, with the benefit of significantly improvedDNA and RNA quality and RNA picogram yield per nucleus as compared with FFPE tissue. For fresh frozen, FFPE, and PFPE tissues, respectively, the average Genomic Quality Numbers were 7.9, 3.2, and 6.2, average RNA Quality Numbers were 8.7, 2.6, and 6.3, average DNA picogram yields per nucleus were 0.41, 0.69, and 0.78, and average RNA picogram yields per nucleus were 1.40, 0.94, and 2.24. These findings suggest that where DNA and/or RNA analysis of tissue is required, and when tissue size is small, PFPE may provide important advantages over FFPE. The results also suggest several interesting nuances including potential avenues to improve RNA quality in FFPE tissues and confirm recent suggestions that some DNA sequence artifacts associated with FFPE can be avoided. Abstract : Supplemental Digital Content is available in the text.